Lightweight Software Transactions for Games - Baldassin, Alexandro; Burckhardt, Sebastian (First USENIX Workshop on Hot Topics in Parallelism, 2009)
To realize the performance potential of multiple cores, software developers must architect their programs for concurrency. Unfortunately, for many applications, threads and locks are difficult to use efficiently and correctly. Thus, researchers have proposed transactional memory as a simpler alternative. To investigate if and how software transactional memory (STM) can help a programmer to parallelize applications, we perform a case study on a game application called SpaceWars3D. After experiencing suboptimal performance, we depart from classic STM designs and propose a programming model that uses long-running, abort-free transactions that rely on user specifications to avoid or resolve conflicts. With this model we achieve the combined goal of competitive performance and improved programmability.